How life and hope association translate the Buddha teachings Into real practice life changing life. - Dharmatinno Lorn Loeurm,, Tipitaka Team K. (1110). Khmer Tipitaka (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2018)
The purpose of the research aimed to study the Buddhist status, knowledge, concepts, and philosophy that can make a change for life especially positive changes which meant that change from suffered to comfortable, change from bad to good, change from blind to wisdom due to applying the Buddha Teaching (Dharma) into their daily life. Is quantitative by taking some stories of some people who were in Buddha time who effectively taken the benefit and advantaged from right applied the Buddha Teaching and they could release themself from suffering even still in this world another research from stories from current people who effectively applied and they can live in a very comfortable life.             In conclusion, so many human beings and living beings have lived with huge suffering caused by needs, desire, greed, jealousy, anger, selfishness, defilements, unwholesome mind and not know how to overcome them, not know what is the real meaning of life, and not know how to live in a peaceful and harmonious way. So that, they have always felt sad when something goes wrong or do not meet their perspective or need such as broken heart, losing a beloved one, fail in business, got sick, etc. They cannot be able to accept but reject and feel it should not be like that and leaves their lives in a suffered mood for years. Buddha's Teaching is the most important to help to heal people's minds to accept the truth of life, the nature of life, and the cycle of born and die and can live in a peaceful, prosperous, and harmonious manner. Keywords : how, LHA, Buddhism, life, and the sublime state of mind.